A dance to the music of time. Vol. 1 [videorecording (DVD)] - Rakoff, Alvin; Morahan, Christopher; Purefoy, James, 1964-; Richardson, Miranda; Gielgud, John, 1904-2000; Powell, Anthony, 1905-2000 (Acorn Media, 2007)
Chronicles a half century of British upper-class life through the eyes of Nicholas Jenkins, from the 1920s to the 1960s. See how friendship, adultery, ambition, and failure play out in London's social, political, and artistic scenes.